Endangered Shark Species Identified in Bintan Island Waters, Riau Island Province, Indonesia - Mutia Dhiya Amani; Rika Permata Sari; Irwan Effendi (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2022)
Shark is one of the fish caught and traded around Bintan Island, Indonesia. There are at least 13 species of shark and of which there are 3 species that are already in endangered status. This research was conducted from January 2 to June 30 at the Padang Coastal Marine Resources Management Center (PCMRMC), Tanjung Pinang Work Unit. The purpose of this study was to identify the species of deep shark whose population is critically endangered and endangered in the waters around Bintan Island, Riau Island Province, Indonesia. Shark identification is done by observing the shark's physical body in whole or in part. Includes color, fin shape, tooth shape, motif. A number of 3 critically endangered and endangered shark species were identified from Bintan Island waters, namely the scalloped hammerhead (Sphyrna lewini Griffith & Smith, 1834), zebra shark (Stegostoma tigrinum), and sandbar shark (Carcharhinus plumbeus). All of these sharks are still caught, consumed and traded in this area. According to the IUCN, the current population conservation status of them is critically endangered (scalloped hammerhead), and endangered (zebra shark and sandbar shark).